Application of cognitive modelling for operation improvement of retail chain management system - Dankeieva, Oksana; Solomyanyuk, Natalia; Strashynska, Larysa; Fiedotova, Nataliia; Soloviova, Yulia; Koval, Viktor (My University, 2021)
The main purpose of the study is to implement cognitive modelling of the retail chain management system to ensure the effectiveness of management decisions to implement structural changes in its activities. It is determined that the organization of retail chain management is more effective provided the principles of a systematic approach are applied. Therefore, using the concept of Balanced Scorecard (BSC) in this study, which reflects the interaction and interdependence of structural units, is feasible and based on which, we propose to further search for development scenarios for the retail chain management. The article presents a sequence of cognitive modelling, which consists of seven main stages. Drogerie format management system of retail chains has been chosen since it has recently been standing out by its popularity with consumers among other formats, as an object for the study. The results of this study can be useful for enterprises and organizations with complex systems that are characterized by hierarchical, network relationships between subsystems or where random processes take place. Основною метою дослідження є впровадження когнітивного моделювання системи управління роздрібною мережею для забезпечення ефективності управлінських рішень щодо здійснення структурних змін у її діяльності. Визначено, що організація управління роздрібною мережею є більш ефективною за умови застосування принципів системного підходу. Тому використання концепції збалансованої системи показників (BSC) у цьому дослідженні, що відображає взаємодію та взаємозалежність структурних підрозділів, є доцільним і на основі якого ми пропонуємо подальший пошук сценаріїв розвитку для управління торговою мережею. У статті представлена ​​послідовність когнітивного моделювання, яка складається з семи основних етапів. Система управління форматом Drogerie для торгових мереж була обрана, оскільки нещодавно вона виділяється своєю популярністю серед споживачів серед інших форматів, як об'єкт дослідження. Результати цього дослідження можуть бути корисними для підприємств та організацій із складними системами, які характеризуються ієрархічними, мережевими взаємозв'язками між підсистемами або де відбуваються випадкові процеси.
Keywords: кафедра маркетингу; retail chains; cognitive map; concept models; concept of balanced scorecard; development scenarios; когнітивна карта; концептуальні моделі; концепція збалансованої системи показників; сценарії розвитку; торгові мережі